Resilience and recovery from an environmental disaster: the journey of child survivors of the Kiteezi landfill in Uganda - Mahadih Kyambade; Luke Sewante; Afulah Namatovu (Cogent Social Sciences)
This study explored the resilience and recovery of child survivors following the 2024 Kiteezi landfill disaster in Uganda, where recurrent landslides displaced families and left lasting emotional, psychological, and social impacts on young survivors. Utilizing a qualitative phenomenological approach, we conducted in-depth interviews with child survivors and their guardians, focusing on their experiences of displacement, trauma, and adaptation in the wake of the disaster. Twenty participants were identified through convenience and snowball sampling, facilitated by local leaders who played a key role in engaging the community and establishing a supportive framework for this research. The findings revealed the depth of trauma experienced by child survivors, marked by vivid memories, sadness, and symptoms of post-traumatic stress. However, a recurring theme of resilience has emerged, with many children finding solace through family support, faith, and community connections. This study highlights the importance of culturally sensitive community-based support systems and trauma-informed care in fostering resilience and aid recovery in young disaster survivors. These insights contribute to broader discussions on children’s mental health, resilience, and the effectiveness of family and community structures in post-disaster recovery, underscoring the need for comprehensive mental health resources to support child survivors in the long term.